CfrA, a Novel Carbon Flow Regulator, Adapts Carbon Metabolism to Nitrogen Deficiency in Cyanobacteria . Issue 4 (8th September 2020) - Muro-Pastor, M. Isabel; Cutillas-Farray, Áureo; Pérez-Rodríguez, Laura; Pérez-Saavedra, Julia; Vega-de Armas, Ana; Paredes, Ana; Robles-Rengel, Rocío; Florencio, Francisco J.
Abstract : Carbon flow regulator A (CfrA) is a novel cyanobacterial regulatory protein involved in the redirection of carbon flow toward glycogen storage in response to nitrogen deficiency. Abstract: Cyanobacteria unable to fix atmospheric nitrogen have evolved sophisticated adaptations to survive to long periods of nitrogen starvation. These genetic programs are still largely unknown—as evidenced by the many proteins whose expression is regulated in response to nitrogen availability, but which belong to unknown or hypothetical categories. In Synechocystis sp. PCC 6803, the global nitrogen regulator NtcA activates the expression of the sll0944 gene upon nitrogen deprivation. This gene encodes a protein that is highly conserved in cyanobacteria, but of unknown function. Based on the results described herein, we named the product of sll0944 carbon flow regulator A (CfrA). We analyzed the phenotypes of strains containing different levels of CfrA, including a knock-out strain (ΔcfrA), and two strains overexpressing CfrA from either the constitutive P trc promoter (Ptrc-cfrA) or the arsenite-inducible promoter P arsB (Pars-cfrA). Our results show that the amount of CfrA determines the accumulation of glycogen, and affects the synthesis of protein and photosynthetic pigments as well as amino acid pools. Strains with high levels of CfrA present high levels of glycogen and a decrease in photosynthetic pigments and protein content when nitrogen is available. Possible interactions between CfrA and the pyruvate dehydrogenase complex or PII protein have been revealed. The phenotype associated with CfrA overexpression is also observed in PII-deficient strains; however, it is lethal in this genetic background. Taken together, our results indicate a role for CfrA in the adaptation of carbon flux during acclimation to nitrogen deficiency.